Pengaruh Islamic Branding Dalam Pemasaran Produk Kepada Konsumen Muslim - Arnova Witiar Nidah; M Iqbal Fasha; Suharto Suharto (FEB Universitas Sultan Ageng Tirtayasa, 2022)
The focus of the discussion in this paper is related to Islamic branding as a marketing strategy to consumers. With the aim of knowing and describing how the influence of Islamic branding in product marketing to Muslim consumers. The method used in this research is qualitative descriptivemethode with a literature study approach with the main data source coming from journals, with the point of view of the Quran, hadith and other related scientific works. This study shows the concept of Islamic branding in accordance with sharia law, which in marketing strategies can have an effect on building Muslim consumer trust. With the halal label from the MUI, consumers will not worry about consuming a product with an Islamic brand because the halalness of the product has been confirmed. With this trust, it will influence consumer decisions and can increase sales of a product.